Revalidation for general practitioners: randomised comparison of two revalidation models. Issue 7441 (18th March 2004) - Bruce, David; Phillips, Katie; Reid, Ross; Snadden, David; Harden, Ronald
Abstract: Objective To compare two models of revalidation for general practitioners. Design Randomised comparison of two revalidation models. Setting Primary care in Tayside, Scotland. Participants 66 Tayside general practitioners (principals and non-principals), 53 of whom completed the revalidation folders. Interventions Two revalidation models: a minimum criterion based model with revalidation as the primary purpose, and an educational outcome model with emphasis on combining revalidation with continuing professional development. Main outcome measures Feasibility and acceptability of each approach and effect on the doctor's continuing professional development. The ability to make a summative judgment on completed models and whether either model would allow patient groups to have confidence in the revalidation process. Results The criterion model was preferred by general practitioners. For both models doctors reported making changes to their practice and felt a positive effect on their continuing professional development. Summative assessment of the folders showed reasonable inter-rater reliability. Conclusions The criterion model provides a practical and acceptable model for general practitioners to use when preparing for revalidation.